1)Բացե՛ք փակագծերն ու բերե՛ք կատարյալ տեսքի.
ա) (x + 3)(x + 6) =x²+3x+18
բ) (3a + 4)(2a − 7) =6a2-21a+8a=-13a
գ) (9x2 − 4x)(9x + 4)=81×3+36×2-36×2=0
-16x
դ) (2y2 − b2)(3y2 + 4b2) =6y4+862y2-362
ե) (a − b)(a + b) =
զ) (7a − 3)(7b + 3) =
2)Բացե՛ք փակագծերն ու միավորե՛ք նման միանդամները.
ա) (ax + 5)(bx − 1) =
բ) (7b2 + 3a3)(3a3 − 7b2) =
գ) (y − 2)(y + 1) =
դ) (−x + 5)(x − 1) =
3)Բերե՛ք կատարյալ տեսքի.
ա) 5(2 − 3c) + 7(3c + 1) =
բ) 6x(x − 2) − 3(2x2 − 4) =
գ) (a + b)( a2 − ab + b2) =
դ) (x + 1)(y + 1) + (x − 1)(y − 1) =